Gathering Empirical Evidence Concerning Links Between Computer Aided Design (CAD) and Creativity - Musta’amal, Aede Hatib; Norman, Eddie; Hodgson, Tony (Design and Technology Education: An International Journal, 2009)
Discussion is often reported concerning potential links between computer-aided designing and creativity, but there is a lack of systematic enquiry to gather empirical evidence concerning such links. This paper reports an indication of findings from other research studies carried out in contexts beyond general education that have sought evidence relating CAD and creativity. It describes the establishment of a framework for gathering empirical evidence to support the analysis of links between CAD and creativity, via the observation of creative behaviours, which was developed from published literature largely relating to the area of cognitive psychology. It notes some initial research findings concerning the use of this framework in analysing the use of CAD in postgraduate design projects completed at Loughborough University. These results demonstrate the occurrence of creative behaviours in association with the use of CAD when designing. Finally the significance of these results is discussed within the wider context of design modelling.